The Handbook of Plant Metabolomics 2013
DOI: 10.1002/9783527669882.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Secondary Metabolism and Transcript Regulation in Arabidopsis Thaliana

Abstract: Metabolic states in plants are dynamically controlled via transcriptional regulation in response to environmental and developmental conditions. However, the regulatory mechanisms between gene expression (input) and the resultant metabolite accumulation (output) remain unclear because complex post-transcriptional events such as feedback regulation and inter-tissue translocation often play important roles in these mechanisms [1]. Hence detailed investigations of the dynamic behavior of metabolic systems and an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…This study showed that gene pairs connected by interactions supported by multiple data are more likely to belong to the same GO category. For example in [ 81 ] gene expression profiles and mass spectrometry profiles are merged by using appropriate normalization of the data and a combined network of genes and metabolites has been constructed which helped find related genes and metabolites. A very large network of more than 60,000 interactions was reported [ 82 ] by integrating transcription factor binding, PPI, and protein phosphorylation data of yeast.…”
Section: Network Analysis In Systems Biologymentioning
confidence: 99%
“…This study showed that gene pairs connected by interactions supported by multiple data are more likely to belong to the same GO category. For example in [ 81 ] gene expression profiles and mass spectrometry profiles are merged by using appropriate normalization of the data and a combined network of genes and metabolites has been constructed which helped find related genes and metabolites. A very large network of more than 60,000 interactions was reported [ 82 ] by integrating transcription factor binding, PPI, and protein phosphorylation data of yeast.…”
Section: Network Analysis In Systems Biologymentioning
confidence: 99%